Catalytic C–C Bond Formation via Aromatic C–H Bond Cleavage Using Low-Valent Iron-Phosphine Complexes - Kakiuchi, Fumitoshi; Kochi, Takuya (Synlett, 2025)
This article presents our findings on catalytic ortho-selective C–C bond formations through the cleavage of C–H bonds in aromatic ketones using low-valent iron-phosphine complexes. We describe four types of catalytic transformations that convert C–H bonds into C–C bonds. Reactions involving terminal alkenes, such as vinyl and allylsilanes, aliphatic alkenes, styrenes, vinyl ethers, and enamines, yield the corresponding linear alkylation products. The coupling reaction using methylenecyclopropanes yields homoallylation products via alkene 1,2-insertion, followed by β-carbon elimination. The C–H alkenylation can be achieved by the reaction with internal alkynes. The use of 1,n-enynes (where n = 6, 7) as coupling partners for the C–H bond led to hydroarylative enyne cyclization products. The results of deuterium-labeling experiments of these reactions are also discussed.
Keywords: Low-valent iron-phosphine complex; C–H activation; C–C bond formation; Aromatic ketone; Alkenes; Alkynes; 1,n-Enynes